Comprehensive characterization of formation rock for tight oil exploitation - Kang, Hao; Zhou, Xinyu; Gao, Jian; Zhang, Chunxiang (Frontiers in Energy Research, 2022)
Although it is generally very difficult to supplement flow energy into the tight oil reservoir, there is still good prospect for enhanced oil and gas recovery in this area due to its large proportion of hydrocarbon reserves. Choosing a tight formation rock in the Northwest part of China as the object of study, general tests are first conducted. After that, porosity and permeability of its core sample are tested under overburden pressure conditions. Studies show that overburden porosity and permeability will decrease but total decrease percentage will increase with the increase of net effective overburden pressure. The decrease percentage of permeability is much higher compared with that of porosity decrease percentage under overburden pressures. When the net effective overburden pressure is larger than 10MPa, the decrease of overburden porosity will become relatively small. When the net effective overburden pressure is larger than 15MPa, the decrease of overburden permeability will become relatively small. Taking the pressure-increasing process and the pressure-decreasing process as a whole: the permeability cannot recover to the initial level when overburden pressure is the same as previous round because certain permeability is permanently damaged in the process. At the same time, when the net effective overburden pressure is in a high level, the permeability damaged will become relatively small. These experiments compose of a comprehensive characterization of formation rock and can be good references for oil and gas exploitation on site in tight reservoirs.